A Case Report of Takayasu’s Arteritis - O.O. Andrushkova; T.M. Zhmud; N.B. Malachkova; K.Iu. Grizhimalskaia; D.A. Iatsenko (Journal of Ophthalmology, 2017)
Background: Takayasu’s arteritis is a non-specific autoimmune disease affecting large-size blood vessels, with a predilection for the aorta and its major branches. The most characteristic symptoms include absence or decrease of arterial pulses in the arms and CNS-related abnormalities (arm numbness, pain and paresthesia; fatigue; dizziness; syncope; seizures; aphasia; and hemipareses).